PERBANDINGAN PENERAPAN MODEL PEMBELAJARAN PROBLEM COMPOSING DENGAN MODEL PEMBELAJARAN PROBLEM POSING TIPE PRE SOLUTION POSING TERHADAP HASIL BELAJAR FISIKA SISWA DI SMAN 72 JAKARTA - Imas Ratna E; Acep Galing K; Ilsa Syabira (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2014)
This study aims to determine whether or not there are comparisons of learning outcomes between students' physics student learning model problem composing with the model type of learning problem posing pre solution posing. The hypothesis of this study is the comparison between the model of learning There is a problem composing learning with model type of problem posing pre solution posing for physics students' learning outcomes. The research was conducted at SMAN 72 Jakarta class XI in the second semester of academic year 2012/2013. The method used in this study is a Quasi Experimental method. With the target population to which all students of SMA Negeri 72 Jakarta, while the population of all students in grade XI inaccessibility IPA. Sampling technique in this study was simple random sampling randomly determined and taken 34 students of class XI IPA 2 as experiment and 34 students of class XI IPA 4 as the control class. Data collection technique using a research instrument multiple choice test. The research instrument before given to the object of research is done before the test instrument validity, reliability testing, test difficulty level, and distinguishing test. 81 Description of the results of the analysis of data obtained an average value of 80.6, while the experimental class control class is 71.5 mean average value of the experimental class higher than the control class. While hypothesis testing using the t test obtained tcount = 4,997 > 1,998 = ttable using a significance level of = 0.05. This means reject H0, then the results of this study concluded that there is a comparison between the model of learning problem composing with the model type of learning problem posing pre solution posing to the physics student learning outcomes. Keywords : Problem Composing Learning Model, Model Type of Learning Problem Posing Pre Solution Posing , Learning Outcomes.